DESENVOLVIMENTO DE PROCESSOS DE COMPATIBILIZAÇÃO EM COMPÓSITO DE POLIETILENO DE ALTA DENSIDADE COM PÓ DE BORRACHA DE PNEU - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
The tires are polymeric materials that are difficult to reuse and recycling due to the presence of steel and molecular structure thereof. The increase in the national fleet of vehicles led to an increase in production and thus dispose of tires. When tires reach the end of life, they become unusable, being most often disposed of improperly. When this occurs there are problems related to public health and the environment. The general objective of this study was to facilitate the reuse of waste tire rubber by incorporating matrix in high density polyethylene (HDPE). In order to improve the interfacial adhesion and final properties sought to reconcile the mix with the addition of ethylene octene-1 (C2C8). The size and distribution of rubber particles from tires were evaluated by the technique of particle size distribution. The morphological characterizations were made in a Raman spectrometer coupled with optical microscopy and scanning electron microscopy (SEM). The mechanical properties were studied by testing the tensile and impact strength, to evaluate them statistical tests were performed. The thermal characterizations were made by differential scanning calorimetry (DSC) and with the aid of thermo-optical analysis of Hot Stage. It was observed through the scanning electron micrographs of the processing performed on twin-screw extruder was effective, resulting in mixtures with good distribution and dispersion. The FT-Raman spectra showed that the compatibilizing agent has not acted on the interface of the mixture and that the powder particles of tire rubber were encapsulated by HDPE. The impact resistance of binary mixtures PEAD/C2C8 showed a significant increase in the mixtures and HDPE / PBP properties were maintained at levels up to 40% of powdered rubber tire (PBP). The blends also exhibited high values of elongation at break compared to the pure polymer, with the samples that showed high values of impact resistance also showed a high deformation. The C2C8 did not act as nucleating agent, and there was a lowering of the melting temperature and crystallization was influenced by cooling rates. A major benefit of this study was the possibility of adding a large quantity of tire rubber powder in the matrix retaining the properties of impact resistance. Accordingly, reduced material costs.
Keywords: Pneus; borracha de pneu; caracterizações; propriedades; tires; rubber tire; characterization; properties; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA